Controlled synthesis of iron oxyhydroxide (FeOOH) nanoparticles using secretory compounds from Chlorella vulgaris microalgae - Ghanbariasad A.; Taghizadeh S.-M.; Show P.L.; Nomanbhay S.; Berenjian A.; Ghasemi Y.; Ebrahiminezhad A. (Taylor and Francis Inc., 2023)
ferric hydroxide; iron oxyhydroxide nanoparticle; nanoparticle; unclassified drug; adsorption; Article; atomic absorption spectrometry; atomic force microscopy; bioremediation; Chlorella vulgaris; drug synthesis; electrochemical analysis; elemental analysis; Fourier transform infrared spectroscopy; microalga; nonhuman; particle size; plant cell; surface property; synapse vesicle; temperature; thermogravimetry; transmission electron microscopy; X ray diffraction; zeta potential